Rancang Bangun Sistem Otomatis dan Monitoring Ruangan Dapur dari Kebakaran Berbasis Internet of Things - Arifin, Samsul; Wilyanti, Sinka; Olivia, Arisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
One of the fires that occurred in the kitchen was an LPG gas leak. To prevent fires from occurring, there was a need for a tool that could dispose of LPG gas leaks in the kitchen. From this problem, a system and tool was created using a Wemos D1 Mini microcontroller which was connected to the MQ-2, DHT 11, IR Flame and PIR sensors and the Blynk application for monitoring remotely with internet of things technology. For the MQ-2 sensor, when it detects gas above 200 ppm, an alarm will sound and activate 1 blower and will activate 2 blowers when it detects gas above 700 ppm. Apart from that, the tool made is also equipped with automatic fire extinguishing settings with an IR Flame sensor, temperature settings with a DHT 11 sensor and light settings with a PIR sensor. The systems and tools created have the benefit of preventing early fires in the kitchen.